Psychometric Properties of Update Arabic Version of the Trait Hope Scale and the Rosenberg Self-Esteem Scale - Hatim Ben Ayad; Nóra Kerekes; Anis Sfendla; Adil Najdi; Meftaha Senhaji (Indonesian Psychological Research, 2024)
Hope and self-esteem are crucial components of positive psychology, and there is a lack of tools to assess these concepts in Morocco. Therefore, this study aims to provide the necessary instruments for evaluating hope and self-esteem among Moroccan college students. A total of 1150 college students (444 males, 703 females) completed an updated Arabic version of the Trait Hope Scale (THS) and the Rosenberg Self-Esteem Scale (RSES). The data underwent factorial and reliability analyses, with test-retest reliability assessed using responses from 26 students. Both the THS and RSES revealed a two-factor solution, and Multigroup Confirmatory Factor Analysis (MGCFA) demonstrated measurement invariance with respect to gender. Furthermore, the results indicated good and acceptable internal consistency (α = .85 for THS and α = .70 for RSES) and acceptable temporal stability (r = .72 for THS and r = .76 for RSES). In conclusion, the updated Arabic versions of the THS and RSES exhibited strong psychometric properties and stability. They have been established as valid and reliable tools for assessing hope and self-esteem among Moroccan college students.